2021
DOI: 10.1111/1365-2664.13977
|View full text |Cite
|
Sign up to set email alerts
|

An unintended ecological benefit from human intervention: The enhancement of carbon storage in seagrass meadows

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The water area is 4.84 km 2 , the mean water depth is 1.2 m, and the maximum depth is 3.8 m. Komuke Lagoon consists of three enclosed basins and is a typical lagoon, which can trap nutrients. Eelgrass ( Z. marina ) inhabits the subtidal zones and contributes to sequestering organic carbon in the sediments (K. Watanabe & Kuwae, 2021). The field observations we conducted in 2018 showed that the salinity range was about 20–34 because of the greater seawater exchange with the Okhotsk Sea than river inflow.…”
Section: Methodsmentioning
confidence: 99%
“…The water area is 4.84 km 2 , the mean water depth is 1.2 m, and the maximum depth is 3.8 m. Komuke Lagoon consists of three enclosed basins and is a typical lagoon, which can trap nutrients. Eelgrass ( Z. marina ) inhabits the subtidal zones and contributes to sequestering organic carbon in the sediments (K. Watanabe & Kuwae, 2021). The field observations we conducted in 2018 showed that the salinity range was about 20–34 because of the greater seawater exchange with the Okhotsk Sea than river inflow.…”
Section: Methodsmentioning
confidence: 99%
“…Seagrasses act as highly effective carbon sinks and can sequester and store substantial amounts of carbon dioxide (CO 2 ) from the atmosphere [297][298][299]. Restoration efforts aimed at seagrass meadows enhance their carbon sequestration capacity, aiding in the mitigation of climate change impacts.…”
Section: Carbon Sequestrationmentioning
confidence: 99%
“…Coastal and marine green infrastructures, such as coral reefs and seagrass meadows, two of the marine ecosystems that receive the most pressure from nautical and recreational activities, such as sport diving on a global scale [10,37], provide key environmental services for the well-being and development of the world's coastal and littoral populations (Table 1). Coral reefs and seagrass meadows provide a series of critical environmental services, such as the protection and defence of coastal populations against increasingly common extreme weather events (devastating rains and floods) linked to climate change, serving as a refuge and breeding areas for marine species which are of interest to the fishing industry, and the mitigation of the greenhouse effect through the fixation of organic carbon (blue carbon) [53,72,75].…”
Section: Introductionmentioning
confidence: 99%